'An Apotheosis of Well-Being': Durkheim on austerity and double-dip recessions. (November 2015) - Dawson, Matt
This article is an attempt to contribute a view on the economic crisis from classical sociology, a voice often missing from the sociological response to the crisis. The work of Émile Durkheim provides a unique perspective here centred on morality and inequality produced in a historical context akin to our neoliberal times. It is argued there are four key points to take from Durkheim's work. First, that the initial credit crunch can be more fully understood with reference to the economic anomie which Durkheim sees as 'chronic' in a time of marketisation. Second, that this creates an antagonistic relationship between a supposedly self-dependent rich and lazy poor. Third, this conception of self-dependency and individual initiative makes any attempt to regulate the economy akin to sacrilege. Finally, the state is unwilling to intervene due to the emergence of 'pseudo-democracies'. Therefore, Durkheim's theory accounts for the initial crisis, austerity and double-dip recessions in a sociological framework. The article concludes by returning to the centrality of morality to the crisis for Durkheim and highlighting the omission of this in contemporary debates.